Association between UCP2 gene 3’UTR I/D and A55V polymorphisms and neural tube defects susceptibility: systematic review, meta-analysis, and trial sequential analysis - Tian, Haokun; Guan, Zhen; Li, Shen; Wang, Jianhua (Frontiers in Neurology, 2024)
Aim Our study aimed to assess the association between UCP2 gene 3’ untranslated region insertion/deletion (3’UTR I/D) and A55V (alanine/valine) polymorphisms and neural tube defects (NTDs) susceptibility. Materials and methods According to pre-determined inclusion and exclusion criteria, the article search was conducted to search articles published before October 2023. Two authors independently screened the included articles and extracted their basic characteristics. After quality evaluation, the meta-analysis and trial sequential analysis (TSA) were conducted using RevMan 5.4, Stata/MP 17, and TSA 0.9.5.10 Beta. Subgroup analysis was conducted based on country and case group composition. Sensitivity analysis was conducted using a one-by-one exclusion method. Begg’s and Egger’s tests were used to evaluate publication bias. Results A total of seven articles were included. Overall meta-analysis revealed significant heterogeneity among the included studies for 3’UTR I/D polymorphism of the UCP2 gene. Significant statistical data indicated that those with the DD genotype and D allele had higher chances of NTD compared to those with the II genotype and the I allele, respectively. The combined result of II vs. ID was not statistically significant. A55V variation showed no statistical significance in the risk of NTD, despite the absence of significant heterogeneity across the included studies. Most of the heterogeneity was resolved after subgrouping, and a higher risk of the ID genotype was found than the II genotype for Chinese people. Genotyping NTD patients or their mothers was not a factor affecting the heterogeneity. Sensitivity analysis and publication bias analysis suggested that positive findings supported our results. Conclusion The UCP2 gene 3’UTR I/D polymorphism increased the likelihood of developing NTDs in the Chinese population, with the D allele being the risk factor, which contributed to the understanding of the genetic basis of NTDs. TSA indicated that more high-quality original studies were needed in the future for further validation.